THE FUTURE OF A REGIONAL HIGHER EDUCATION INSTITUTION WITHIN THE CONTEXT OF STRATEGIC DEVELOPMENT OF NATIONAL EDUCATION - Igor N. Kim (Высшее образование в России)
Higher education modernization that takes place in the country makes many lecturers from the provinces think that their education institutions somehow fall out of the strategy of national education development. However at the time being regional higher education institution has almost infinite opportunities to develop and improve its educational activities.There is a need for regional higher education institutions to get restructured and turn into scientific and innovative university complexes for successful establishment and effective functioning. An additional point is that university must have its own distinctive feature that will serve as its brand and will make it possible to differentiate it from other universities of the region. These components will ensure a high scientific and educational level as well as integrated training of human resources in order to prepare them for innovative activities and involve the university into an active social and economical development of the region.